PENGGUNAAN MEDIA HIPNOSIS DALAM PEMBELAJARAN BAHASA ARAB MADRASAH IBTIDAIYAH - Hasan Hasan (Program Studi PGMI STAI Al Falah Banjarbaru, 2018)
Hypnosis is a branch of psychology that is searching for the influence of hypnosis and suggestive thoughts are also known to medicine. Hypnosis combined with teaching, known as hypnotizing. Hypnoteaching is a method of learning that in presenting the subject matter, the teacher uses techniques of communicating a very persuasive and suggestive with the goal of keeping the students easily understand the subject matter. Teachers can use it are expected to be medium for teaching with the purpose of developing the motivation of learners in this madrasah ibtidaiyah aged children are particularly in the Arabic language. Hypnosis is also used to enhance their confidence and held in the learning without tension and anxiety, and fear so as to increase their learning outcomes. Hypnoteaching includes the following steps: 1) embed the intentions and motivations in learners; 2) pacing or liken position, gestures, language, as well as brain waves with others or learners; 3) leading or directing the learners; 4) using positive words; 5) giving praise and thanks; 6) modeling or give example through speech and behavior. If teachers applying learning activities in hypnotizing, then the learning atmosphere in the class would be more conducive, learners feel safe and comfortable is important, so that the goal of learning is more easily achieved. Keywords: Psychology, Hypnosis, Media of learning the Arabic language